Sosialisasi Moderasi Beragama Untuk Menumbuhkan Sikap Toleransi: Studi Di SD Negeri Wonokerto - Yazida Wafiy Nurhaq; Mira Puspita Anggraini; Izza Regista Nur Laili; Ikfi Ana Mahfudloh; Ki Ina Rusulu Ana (Aktualisasi Pengabdian Masyarakat, 2025)
The religious moderation socialization program at SDN Wonokerto aims to instill values of tolerance, mutual respect, and harmony from an early age. This activity was initiated due to the lack of contextual delivery of religious moderation materials in schools. The method used was Participatory Action Research (PAR), consisting of observation, approach, organization, planning, action, evaluation, and reflection stages. The implementation involved the active participation of students, teachers, and school staff through discussions, educational games, and direct practice in applying moderation values. The results showed an improvement in students’ understanding and attitudes towards respecting differences, behaving politely, and maintaining harmonious relationships both at school and in the community. Students’ enthusiasm was evident through their active engagement in each session and the application of moderation values in daily interactions. In conclusion, interactive, participatory, and contextual socialization is effective in shaping tolerant and inclusive character. This program has the potential to become a model for character development based on religious moderation that can be integrated into learning and extracurricular activities.